Morphological, immunohistochemical and mirna21 expression manifestations related to cellular apoptosis in focal cerebral ischemia in a rat alcoholism model - Tirapelli, D. P.C.; Cirino, M. L.A.; da Silva, J. P.; Gula, I. S.; Tazima, M. F.G.S.; Fazan, V. P.S.; de Carvalho, C. A.M.; Novais, P. C.; Lizarte Neto, F. S.; Durand, M. T.; Schimming, B. C. [UNESP]; Carlotti Junior, C. G.; et al. (Genetics and Molecular Research, 2020)
Cerebral ischemia is one of the main causes of morbidity and mortality as Abusive use of alcohol also causes health problems, along with considerable social and economic repercussions. We examined how these two conditions affect histopathological signs, morphometrics, expression of apoptosis-related proteins CASPASE 3 and BCL2, and serum gene expression of miRNA-21, in cerebral ischemia associated with a chronic alcoholism model in brain tissue (striatum, lateral and dorsolteral cortex). Fifty adult Wistar rats were divided into five groups: control (C), sham (S), ischemic (I), alcoholic (A) and ischemic/alcoholic groups (I+A). Brain samples were processed for histopathological, morphological, and immunohistochemical analyses for the expression of CASPASE 3 and BCL2, and blood was collected for analysis of miRNA-21 gene expression by real-time PCR. Histopathological changes such as neurons with pyknotic nuclei and diffuse neurons with loss of the contour of their cellular membranes and cytoplasmic edema, were observed in groups I and I+A in all three areas. Protein expression of CASPASE 3 was significantly higher than that of BCL2, with higher expression in groups I and I+A for these two proteins. Serum expression of miRNA-21 was low in all groups, and was slightly higher in groups I and I+A, with no significant differences. The histopathological and morphometric alterations, which were observed mainly in the ischemic animals, correlated with the expression of CASPASE 3. The expression of BCL2 was greater where histopathological changes and expression of CASPASE 3 were less evident. The I and I+A groups presented more histopathological changes, with greater neuronal loss and cerebral edema, and greater expression of CASPASE 3, suggesting that ischemia and alcoholism, when associated, can cause considerable injury and damage to brain tissue.
Keywords: Alcoholism; Apoptosis; Cerebral ischemia; MiRNA-21; Morphology